Strategi penanganan pasca panen padi di Kecamatan Makale Kabupaten Tana Toraja Sulawesi Selatan - Sa'pang; Syamsul Rahman; Musdalifah Mahmud (LP3M Universitas Putra Bangsa, 2026)
Tana Toraja Regency is known for its hilly topography and fertile soil, which support a rice paddy farming system. However, significant challenges remain in post-harvest management. According to this report, most farmers in Makale District still rely on traditional methods for post-harvest activities such as threshing, drying, milling, and storing rice. This results in high post-harvest loss rates, ranging from 10% to 20%, significantly higher than the national average of 8%-10%. This study uses the SWOT Analysis Method used to evaluate strengths, weaknesses, opportunities and threats in the implementation of rice post-harvest handling strategies. The results of this analysis can be used to formulate recommendations for more effective and sustainable strategies for farmers and other stakeholders. The results of the study by carrying out a SWOT analysis include strengths including long experience, farmer group socialization, quality awareness, weaknesses including dominant age old, limited capital, traditional methods, high yield loss, opportunities including government programs, local rice demand, the role of extension workers, the availability of appropriate technology and Threats including extreme weather, competition with modern areas, limited infrastructure, low farmer regeneration. This study emphasizes the importance of transforming harvest-post-harvest practices from traditional to semi-modern based on farmer groups. A combination of training, provision of tools and ongoing support is essential to reduce yield losses, improve grain quality and maintain agricultural sustainability in Tana Toraja